2010
DOI: 10.1097/mpa.0b013e3181c0dd8f
|View full text |Cite
|
Sign up to set email alerts
|

P38α-Selective Mitogen-Activated Protein Kinase Inhibitor for Improvement of Cultured Human Islet Recovery

Abstract: Objectives We investigated whether the recovery of cultured human islets is improved through the addition of a p38α-selective mitogen activated protein kinase inhibitor, SD-282, to clinically used serum-free culture medium. Methods Immediately after isolation, islets were cultured for 24 hours in medium alone (control) or medium containing DMSO, 0.1 μM or 0.3 μM SD-282. Cytokine expression, apoptotic β cell percentage, and islet function were assessed post-culture. Results Expression of p38 and phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…The decrease in BBC3 mRNA was, in part, supported by the decrease in TNF mRNA expression as shown in Fig. 1d, as well as by previous findings presented by ourselves [37] and others [33]. Upregulation of BBC3 is associated with translocation of mitochondria to the perinuclear area and partial colocalisation of BBC3 with mitochondria (Fig.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The decrease in BBC3 mRNA was, in part, supported by the decrease in TNF mRNA expression as shown in Fig. 1d, as well as by previous findings presented by ourselves [37] and others [33]. Upregulation of BBC3 is associated with translocation of mitochondria to the perinuclear area and partial colocalisation of BBC3 with mitochondria (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Human islets were incubated for 1 h with several compounds (listed below), stimulated by TNF-α (5 ng/ml) for an additional 4 h, and expression of BBC3, IL8 and TNF was measured. Compounds were selected on the basis of their specific traits: (1) etanercept, a TNF-α receptor blocker reported to improve glycaemic control in clinical trials in patients with type 1 diabetes [34]; (2) FK506, ciclosporin A and rapamycin, clinically used immunosuppressants that modulate inflammatory/immune reactions; (3) imatinib mesylate, a tyrosine kinase inhibitor that suppresses NF-κB activation and has been shown to protect islets from combined cytokines in vitro and to prevent spontaneous onset of diabetes in NOD mice [35]; and (4) SB203580, a p38 mitogen-activated protein kinase inhibitor that has been shown to prevent beta cell death, in part, by regulating TNF-α abundance [32,36,37]. Pre-incubation of islets with etanercept prevented TNF-α-induced upregulation of BBC3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…No significant difference in TNF-α expression in overnight-cultured experimental and control islets may be due to the decay of p38IH effect, decreased acinar and monocytes numbers, or both. However, it is likely due to the decay of p38IH effect, since we have shown significant improvement of cultured human islets by adding p38IH in the culture medium (41). …”
Section: Discussionmentioning
confidence: 98%
“…Stress, which is generated throughout the procedure for isolating islets, activates proinflammatory signaling pathways and the destruction of β cells . JNK and p38 are preferentially activated in response to the processing of islets for transplantation and by the inflammation associated with islet transplantation . We reported that treatment with peptide inhibitors of JNK during preservation of the pancreas before islet isolation, islet culture, or islet transplantation prevents islet apoptosis and enhances engraftment of islets in vivo .…”
Section: Introductionmentioning
confidence: 99%